2010
DOI: 10.1111/j.1365-313x.2010.04264.x
|View full text |Cite
|
Sign up to set email alerts
|

A rice fungal MAMP‐responsive MAPK cascade regulates metabolic flow to antimicrobial metabolite synthesis

Abstract: Plants recognize potential microbial pathogens through microbial-associated molecular patterns (MAMPs) and activate a series of defense responses, including cell death and the production of reactive oxygen species (ROS) and diverse anti-microbial secondary metabolites. Mitogen-activated protein kinase (MAPK) cascades are known to play a pivotal role in mediating MAMP signals; however, the signaling pathway from a MAPK cascade to the activation of defense responses is poorly understood. Here, we found in rice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
212
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(220 citation statements)
references
References 75 publications
2
212
0
6
Order By: Relevance
“…Remarkably, several TF and MAPK cascade genes acting downstream of SERF1 are activated upon induced expression of MKK4 DD in rice protoplasts, including DREB2A, ZFP179, MAP3K6, and MAPK5 (Kishi- Kaboshi et al, 2010). In addition, it was demonstrated that MAPK5 is phosphorylated by MKK4 (Kishi-Kaboshi et al, 2010), suggesting that SERF1 acts not only upstream but also downstream of a salt-responsive MAPK cascade.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Remarkably, several TF and MAPK cascade genes acting downstream of SERF1 are activated upon induced expression of MKK4 DD in rice protoplasts, including DREB2A, ZFP179, MAP3K6, and MAPK5 (Kishi- Kaboshi et al, 2010). In addition, it was demonstrated that MAPK5 is phosphorylated by MKK4 (Kishi-Kaboshi et al, 2010), suggesting that SERF1 acts not only upstream but also downstream of a salt-responsive MAPK cascade.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, it was demonstrated that MAPK5 is phosphorylated by MKK4 (Kishi-Kaboshi et al, 2010), suggesting that SERF1 acts not only upstream but also downstream of a salt-responsive MAPK cascade. Because in wild-type plants, all direct SERF1 targets are induced within 30 min of salt stress (Figure 4), well before the maximum induction of SERF1 ( Figure 1A), it is likely that the early activation of target genes during salt stress does not exclusively occur through the de novo protein synthesis of SERF1 but also by an already present SERF1 protein, which is activated upon salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…2, 4,205 and 5,267 probe sets were induced and repressed, respectively, in GmMPK4-silenced plants, demonstrating that a massive transcriptome reprogramming occurred. Such altered mRNA transcript profiles were not unexpected, because similar dramatic transcriptome changes have been previously shown in rice plants overexpressing OsMKK4 DD (Kishi-Kaboshi et al, 2010). Because of the extensive changes in gene expression, we analyzed the expression of 48 rRNA soybean probe sets and found that only one rRNA gene was identified as differentially expressed between vector control and GmMPK4-silenced plants (soybean_rRNA_1692_RC_at; P = 0.00085, q = 0.003; Supplemental Table S2).…”
Section: Microarray Analysismentioning
confidence: 99%
“…MPK4 phosphorylation upon Pseudomonas syringae infection of Arabidopsis, released MKS1 and WRKY33, which induced the biosynthesis of camalexin (Rushton et al, 2010). In rice, OsMKK4-OsMPK4/MPK6 play crucial roles in regulating the biosynthesis of diterpenoid-and phenylpropanoid-derived phytoalexins and also lignins in response to a fungal chitin elicitor of M. oryzae (KishiÀKaboshi et al, 2010). In maize following Fusarium verticillioides infection, brassinosteroid-insensitive-1-associated receptor kinase 1 (BAK1) and homologs of AtMKK4 were associated with ear rot resistance (Lanubile et al, 2014).…”
Section: Mitogen-activated Protein Kinase (Mapk) Genes and Regulatmentioning
confidence: 99%